(untitled) (International journal of artificial intelligence, 2026)
This article examines the ecological, aesthetic, and functional principles of landscape design and green element selection in the context of sustainable urban development. The study is conducted with consideration of Uzbekistan’s climatic conditions, limited water resources, and the use of locally adapted plant species. The results highlight the role of green infrastructure in improving urban microclimate, enhancing environmental balance, and increasing the overall quality of urban life. The findings provide practical insights for integrating sustainable landscape solutions into contemporary urban planning strategies.